A method for preparing AgWCC electrical contact material with high toughness structure gradient distribution

By introducing gradient-distributed AgC and pure Ag layers into the AgWCC electrical contact material, combining the deWC and decarbonization processes, the problems of material mechanical fatigue and contact resistance rise are solved, and low contact resistance, fatigue resistance and burn-out resistance are achieved. The effect extends the service life of the circuit breaker.

CN115672836BActive Publication Date: 2024-12-31ZHEJIANG FUDA ALLOY MATERIALS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211236128.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-10
Publication Date
2024-12-31
Estimated Expiration
2042-10-10

AI Technical Summary

Technical Problem

During use, AgWCC electrical contact materials are prone to mechanical fatigue failure, resulting in microcracking, cracking and stratification. The oxidation of WC particles forms WO3, causing a rise in contact resistance and a rise in the circuit breaker temperature, affecting the electrical life.

Method used

The preparation method of AgWCC electrical contact material with high toughness tissue gradient distribution includes a central AgWCC layer, a wrapped AgC layer and a pure Ag layer. Through powder mixing granulation, sintering, surface deWC, decarbonization and recompression processes, the working surface is formed without any WC, high toughness pure Ag layer on the side ensures low contact resistance and mechanical fatigue resistance of the material.

Benefits of technology

It achieves low contact resistance, high stability, good fatigue resistance of the material, and has anti-burn and anti-welding capabilities, extending the service life and safety of the circuit breaker.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115672836B_ABST
    Figure CN115672836B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of electrical contact materials, and specifically to an AgWCC electrical contact material with a high-toughness tissue gradient distribution and a preparation method thereof. It includes a central AgWCC layer, an AgC layer wrapped outside the central AgWCC layer, and a pure Ag layer wrapped outside the AgC layer, wherein one side of the pure Ag layer is open so that one side of the AgC layer is exposed to form a working surface. Since the working surface component is AgC and there is no WC, a stable contact resistance and anti-welding ability are provided for the switch device; since the outermost layer on the side of the material is pure Ag, a high-toughness material, good mechanical fatigue resistance can be provided for the switch device; the central material AgWCC provides good anti-burning and anti-welding capabilities for the switch device during short-circuit current or in the middle and late stages of use, thereby ensuring the safety of electrical appliances. In summary, the AgWCC electrical contact material of the present invention is an ideal electrical contact material with low and stable contact resistance, high toughness, good fatigue resistance, and taking into account anti-burning and anti-welding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electrical contact materials, and in particular to a method for preparing an AgWCC electrical contact material with a high-toughness tissue gradient distribution. Background Art

[0002] AgWCC electrical contact material is one of the most important and largest-volume static contact materials for circuit breakers. AgWCC material is generally made using powder metallurgy. AgWCC material usually contains 1-3wt% C particles, which do not diffuse or sinter with Ag and WC particles in the material. While C particles provide the material with anti-adhesion and breaking properties, they also reduce the material's ability to resist mechanical fatigue. During use, especially in some high-breaking molded case circuit breakers, due to the limitations of the contact bridge structure, the stress is concentrated at the C particles during the use of the material, which can easily cause mechanical fatigue failures such as microcracks, cracks, and even delamination of the AgWCC electrical contact material during use.

[0003] The presence of WC particles in AgWCC material improves the material's ability to resist arc erosion and increases its electrical life. At the same time, WC will oxidize to WO3 under arc, and WO3 is a non-conductive material, which will cause the contact resistance of the contact material to increase, which is manifested in the circuit breaker as an increase in the circuit breaker's operating temperature. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a method for preparing an AgWCC electrical contact material with a high-toughness tissue gradient distribution.

[0005] The first aspect of the present invention provides an AgWCC electrical contact material with a high-toughness organization gradient distribution, which includes a central AgWCC layer, an AgC layer wrapped outside the central AgWCC layer, and a pure Ag layer wrapped outside the AgC layer, wherein one side of the pure Ag layer is open so that one side of the AgC layer is exposed to form a working surface. The above-mentioned AgWCC electrical contact material is a high-toughness material with a WC gradient growth from the working surface to the center, and a gradient growth of WC and C from the welding surface to the center. Since the working surface component is AgC and there is no WC, it provides a stable contact resistance and anti-welding ability for the switch device; since the outermost layer of the material side is a high-toughness material pure Ag, it can provide the switch device with good mechanical fatigue resistance; the central material AgWCC provides the switch device with good anti-burning and anti-welding ability in the short-circuit current or in the middle and late stages of use, ensuring the safety of electrical use. In summary, the AgWCC electrical contact material of the present invention is an ideal electrical contact material with low and stable contact resistance, high toughness, good fatigue resistance, and at the same time taking into account anti-burning and anti-welding.

[0006] The second aspect of the present invention provides a method for preparing the AgWCC electrical contact material with high toughness structure gradient distribution as described above, characterized by comprising the following steps:

[0007] (1) Mixed powder, granulation, molding and sintering: Ag powder, WC powder and C powder are mixed to obtain a uniform mixed powder, which is then granulated and molded. The molded green compact is sintered to obtain a sintered AgWCC green compact;

[0008] (2) Surface WC removal treatment: the sintered AgWCC compact is placed in a silver crucible filled with NaOH, compressed air is introduced, the crucible is heated and kept warm to remove WC particles on the surface of the compact, the WC removal layer depth is 50-100 μm, and the surface WC-removed AgWCC compact is obtained;

[0009] (3) Decarburization: The surface-WC-removed AgWCC compact is cleaned and dried, and then transferred to a decarburization furnace to remove the surface C layer at high temperature. The decarburization depth is 25-50 μm, and the depth is not higher than the depth of the WC-removed layer, to obtain a surface-WC-removed AgWCC compact;

[0010] (4) Removing the decarburized layer on one side: fixing the AgWCC compact with the surface layer decarburized, and removing the decarburized layer on the working surface by grinding or milling to obtain an AgWCC semi-finished product;

[0011] (5) Re-pressing: The AgWCC semi-finished product is cleaned and dried and then re-pressed on a re-pressing machine to obtain an AgWCC electrical contact material with a high-toughness microstructure gradient distribution.

[0012] Preferably, in step (2), the heating temperature is 350-550°C, the heating time is 0.5-4.0h, and the compressed air flow rate is 0.5-2m 3 / h.

[0013] Preferably, the high-temperature decarburization in step (3) is carried out at a decarburization temperature of 600-800° C. and a decarburization time of 5-20 min.

[0014] Preferably, in step (4), the specific process of removing the decarburized layer on one side is as follows: placing the compact on a grinding disc, heating the adhesive to make it liquid and connect it between the compact and the grinding disc, and after the adhesive cools, the compact is bonded to the grinding disc, and abrasives and additives are continuously dripped on a single-sided grinder to grind away the decarburized layer on the working surface. After grinding, the adhesive is dissolved with an organic solvent to remove the compact from the grinding disc.

[0015] Preferably, the adhesive is paraffin, the organic solvent is gasoline, the abrasive is diamond polishing liquid, and the additive is a 15wt% hydrogen peroxide solution.

[0016] Preferably, in step (1), the raw material components are in the following mass fractions: Ag: 70-85wt%; WC: 12-27wt%; C: 1-3wt%.

[0017] The preparation method has the following beneficial effects:

[0018] 1. Use molten NaOH and compressed air to remove WC on the shallow surface of AgWCC electrical contact material without damaging the surface C material. When WC particles are removed, WO3 with low density will not be generated to cause material deformation. During the WC removal process, the overall appearance, shape and size of the material will not change, which is conducive to the smooth progress of subsequent processing.

[0019] 2. The present invention optimizes the single-sided grinding process so that Ag-based small-sized materials can be smoothly ground to remove the surface decarburized surface. The paraffin-gasoline system is used to fix or release the AgWCC electrical contact material and the grinding disc, and the paraffin can be reused. The diamond and hydrogen peroxide abrasive system is used to convert the AgWCC surface material and Ag grinding chips from Ag to Ag2O during the grinding process, making the surface material easier to grind, while reducing the problem of grinding chips stuck on the grinding wheel, which makes it impossible to grind in the later stage. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still belong to the scope of the present invention.

[0021] Figure 1 This is the metallographic phase 1000X of the working surface provided by the embodiment of the present invention, the upper part is made of AgC, and the lower part is made of AgWCC material;

[0022] Figure 2 It is the bottom metallographic image 500X provided by the embodiment of the present invention, which is pure Ag, AgC, and AgWCC materials from bottom to top;

[0023] Figure 3 It is a schematic diagram of the AgWCC material of the present invention. The bottom Ag layer is used for welding, the side Ag layer is used to improve the mechanical fatigue resistance, the working surface AgC layer provides low and stable contact resistance and anti-welding ability for the contact when in contact, and the central AgWCC ensures the material's anti-burning and anti-welding ability. DETAILED DESCRIPTION

[0024] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.

[0025] Example 1

[0026] Ag powder, WC powder and C powder are mixed in a weight ratio of 77.5:20:2.5, and a sintered AgWC20C2.5 compact is obtained by mixing, granulating, molding and sintering in a conventional manner;

[0027] The sintered AgWC20C2.5 compact was placed in a silver crucible, heated to 400°C, NaOH was added and heated to melt to ensure that the molten NaOH submerged the compact, air was introduced into the crucible at an air flow rate of 0.5 m³ / hour, and the crucible was kept warm for 2 hours. The thickness of the WC removal layer was detected to be 50 μm.

[0028] The compact was cleaned and dried, and then transferred to a high-temperature decarburization furnace with a decarburization temperature of 600°C, a decarburization time of 7 minutes, and a decarburization depth of 25 μm.

[0029] Place the decarburized compact on the grinding disc, heat the grinding disc until the paraffin melts and adheres to the compact, place the grinding disc on the single-sided grinder, open the valves of diamond abrasive and hydrogen peroxide and continue to drip until the grinding is completed, set the grinding equipment to a grinding depth of 25μm, and remove the decarburized layer on the working surface. Put the ground compact and grinding disc into gasoline to dissolve the paraffin and separate the compact and grinding disc.

[0030] The ground compact was cleaned and then re-pressed to make it dense at a re-pressing pressure of 900 MPa to obtain AgWC20C2.5 electrical contact material with high toughness and gradient distribution of microstructure.

[0031] The obtained AgWC20C2.5 electrical contact material is used as static contact in 125A circuit breaker, the temperature rise of the circuit breaker is reduced by 5K, and the maximum mechanical life is increased by an average of 3000 times.

[0032] Example 2

[0033] Ag powder, WC powder and C powder are mixed in a weight ratio of 75:22:3, and a sintered AgWC22C3 compact is obtained by mixing, granulating, molding and sintering in a conventional manner;

[0034] The sintered AgWC22C3 material was placed in a silver crucible, and the silver crucible was heated to 550°C. NaOH was added and heated until it was melted to ensure that the molten NaOH submerged the pressed green sheet. Air was introduced into the crucible at an air flow rate of 1.0 m³ / hour. The crucible was kept warm for 0.5 hours. The thickness of the WC removal layer was detected to be 80 μm.

[0035] The compact was cleaned, dried and transferred to a high-temperature decarburization furnace with a decarburization temperature of 800°C, a decarburization time of 5 minutes and a decarburization depth of 30 μm.

[0036] Place the decarburized compact on the grinding disc, heat the grinding disc until the paraffin melts and adheres to the compact, place the grinding disc on the single-sided grinder, open the valves of diamond abrasive and hydrogen peroxide and continue to drip until the grinding is completed, set the grinding equipment to a grinding depth of 35μm, and remove the decarburized layer on the working surface. Put the ground compact and grinding disc into gasoline to dissolve the paraffin and separate the compact and grinding disc.

[0037] The ground compact is cleaned and then re-pressed to make it compact at a re-pressing pressure of 1000 MPa to obtain AgWC22C3 electrical contact material with high toughness and gradient distribution of the microstructure.

[0038] The obtained AgWC22C3 electrical contact material is used as static contact in 250A circuit breaker, the temperature rise of the circuit breaker is reduced by 7K, and the maximum mechanical life is increased by an average of 3200 times.

[0039] Example 3

[0040] Ag powder, WC powder and C powder are mixed in a weight ratio of 73:25:2, and a sintered AgWC25C2 compact is obtained by mixing, granulating, molding and sintering in a conventional manner;

[0041] The sintered AgWC25C2 material was placed in a silver crucible, and the silver crucible was heated to 350°C. NaOH was added and heated until it was melted to ensure that the molten NaOH submerged the pressed green sheet. Air was introduced into the crucible at an air flow rate of 2.0 m³ / hour. The crucible was kept warm for 3 hours. The thickness of the WC removal layer was detected to be 60 μm.

[0042] The compact was cleaned, dried and transferred to a high-temperature decarburization furnace with a decarburization temperature of 700°C, a decarburization time of 10 minutes and a decarburization depth of 35 μm.

[0043] Place the decarburized compact on the grinding disc, heat the grinding disc until the paraffin melts and adheres to the compact, place the grinding disc on the single-sided grinder, open the valves of diamond abrasive and hydrogen peroxide and continue to drip until the grinding is completed, set the grinding equipment to a grinding depth of 40μm, and remove the decarburized layer on the working surface. Put the ground compact and grinding disc into gasoline to dissolve the paraffin and separate the compact and grinding disc.

[0044] The ground compact is cleaned and then re-pressed to make it compact at a re-pressing pressure of 1300 MPa to obtain AgWC25C2 electrical contact material with high toughness and gradient distribution of the microstructure.

[0045] The obtained AgWC25C2 electrical contact material is used as static contact in 400A circuit breakers, the temperature rise of the circuit breaker is reduced by 4K, and the maximum mechanical life is increased by an average of 1,300 times.

[0046] Example 4

[0047] Ag powder, WC powder and C powder are mixed in a weight ratio of 83:15:2, and a sintered AgWC15C2 compact is obtained by mixing, granulating, molding and sintering in a conventional manner;

[0048] Put the sintered AgWC15C2 material into a silver crucible, heat the silver crucible to 500℃, add NaOH and heat until it melts to ensure that the molten NaOH immerses the pressed green sheet, introduce air into the crucible with an air flow rate of 1.5m³ / hour, keep warm for 4 hours, and detect the thickness of the WC removal layer to be 100μm.

[0049] The compact was cleaned, dried and transferred to a high-temperature decarburization furnace with a decarburization temperature of 800°C, a decarburization time of 20 minutes and a decarburization depth of 50 μm.

[0050] Place the decarburized compact on the grinding disc, heat the grinding disc until the paraffin melts and adheres to the compact, place the grinding disc on the single-sided grinder, open the valves of diamond abrasive and hydrogen peroxide and continue to drip until the grinding is completed, set the grinding equipment to a grinding depth of 55μm, and remove the decarburized layer on the working surface. Put the ground compact and grinding disc into gasoline to dissolve the paraffin and separate the compact and grinding disc.

[0051] The ground compact is cleaned and then re-pressed to make it compact at a re-pressing pressure of 1200 MPa to obtain AgWC15C2 electrical contact material with high toughness and gradient distribution of the microstructure.

[0052] The obtained AgWC15C2 electrical contact material is used as static contact in 630A circuit breaker, the temperature rise of the circuit breaker is reduced by 10K, and the maximum mechanical life is increased by an average of 1500 times.

[0053] Example 5

[0054] Ag powder, WC powder and C powder are mixed in a weight ratio of 70:27:3, and a sintered AgWC27C3 compact is obtained by mixing, granulating, molding and sintering in a conventional manner;

[0055] The sintered AgWC27C3 material was placed in a silver crucible, and the silver crucible was heated to 550°C. NaOH was added and heated until it was melted to ensure that the molten NaOH submerged the pressed green sheet. Air was introduced into the crucible at an air flow rate of 1.8 m³ / hour. The crucible was kept warm for 3.5 hours. The thickness of the WC removal layer was detected to be 80 μm.

[0056] The compact was cleaned, dried and transferred to a high-temperature decarburization furnace with a decarburization temperature of 750°C, a decarburization time of 15 minutes and a decarburization depth of 40 μm.

[0057] Place the decarburized compact on the grinding disc, heat the grinding disc until the paraffin melts and adheres to the compact, place the grinding disc on the single-sided grinder, open the valves of diamond abrasive and hydrogen peroxide and continue to drip until the grinding is completed, set the grinding equipment to a grinding depth of 45μm, and remove the decarburized layer on the working surface. Put the ground compact and grinding disc into gasoline to dissolve the paraffin and separate the compact from the grinding disc.

[0058] The ground compact was cleaned and then re-pressed to make it compact at a re-pressing pressure of 1100 MPa to obtain AgWC27C3 electrical contact material with high toughness and gradient distribution of the microstructure.

[0059] The obtained AgWC27C3 electrical contact material is used as static contact in 160A circuit breaker, the temperature rise of the circuit breaker is reduced by 8K, and the maximum mechanical life is increased by an average of 2700 times.

[0060] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.

Claims

1. A method for preparing a high-toughness AgWCC electrical contact material with a gradient distribution of tissue, characterized in that: The AgWCC electrical contact material comprises a central AgWCC layer, an AgC layer wrapped outside the central AgWCC layer, and a pure Ag layer wrapped outside the AgC layer, wherein one side of the pure Ag layer is open so that one side of the AgC layer is exposed to form a working surface; The preparation method comprises the following steps: (1) Mixed powder, granulation, molding and sintering: Ag powder, WC powder and C powder are mixed to obtain a uniform mixed powder, which is then granulated and molded. The molded green compact is sintered to obtain a sintered AgWCC green compact; (2) Surface WC removal treatment: the sintered AgWCC compact is placed in a silver crucible filled with NaOH, compressed air is introduced, the crucible is heated and kept warm to remove WC particles on the surface of the compact, the WC removal layer depth is 50-100 μm, and the surface WC-removed AgWCC compact is obtained; (3) Decarburization: The surface-WC-removed AgWCC compact is cleaned and dried, and then transferred to a decarburization furnace to remove the surface C layer at high temperature. The decarburization depth is 25-50 μm, and the depth is not higher than the depth of the WC-removed layer, to obtain a surface-WC-removed AgWCC compact; (4) Removing the decarburized layer on one side: fixing the AgWCC compact with the WC and C removed from the surface, and removing the decarburized layer on the working surface by grinding or milling to obtain an AgWCC semi-finished product; (5) Re-pressing: The AgWCC semi-finished product is cleaned and dried and then re-pressed on a re-pressing machine to obtain an AgWCC electrical contact material with a high-toughness microstructure gradient distribution.

2. The method for preparing the AgWCC electrical contact material with high toughness structure gradient distribution according to claim 1, characterized in that: In step (2), the heating temperature is 350-550°C, the heating time is 0.5-4.0h, and the compressed air flow rate is 0.5-2m 3 / h.

3. The method for preparing the AgWCC electrical contact material with high toughness structure gradient distribution according to claim 1, characterized in that: The high-temperature decarburization in step (3) has a decarburization temperature of 600-800°C and a decarburization time of 5-20 minutes.

4. The method for preparing the AgWCC electrical contact material with high toughness structure gradient distribution according to claim 1, characterized in that: In step (4), the specific process of removing the decarburized layer on one side is as follows: placing the compact on a grinding disc, heating the adhesive to make it liquid and connect it between the compact and the grinding disc, and after the adhesive cools, the compact is bonded to the grinding disc, and abrasives and additives are continuously dripped on a single-sided grinder to grind and remove the decarburized layer on the working surface. After grinding, the adhesive is dissolved with an organic solvent to remove the compact from the grinding disc.

5. The method for preparing the AgWCC electrical contact material with high toughness structure gradient distribution according to claim 4, characterized in that: The adhesive is paraffin, the organic solvent is gasoline, the abrasive is diamond grinding fluid, and the additive is a 15wt% hydrogen peroxide solution.

6. The method for preparing the AgWCC electrical contact material with high toughness structure gradient distribution according to claim 1, characterized in that: In step (1), the raw material components are as follows: Ag: 70-85wt%; WC: 12-27wt%; C: 1-3wt%.